2018
DOI: 10.1002/2017jg004026
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Methane and Sources of High Concentrations in Los Angeles Groundwater

Abstract: In 2014, samples from 37 monitoring wells at 17 locations, within or near oil fields, and one site >5 km from oil fields, in the Los Angeles Basin, California, were analyzed for dissolved hydrocarbon gas isotopes and abundances. The wells sample a variety of depths of an aquifer system composed of unconsolidated and semiconsolidated sediments under various conditions of confinement. Concentrations of methane in groundwater samples ranged from 0.002 to 150 mg/L—some of the highest concentrations reported in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…13,37 Within a given lithology group, methane concentrations are typically higher in younger sediments than in older sediments, 13 and higher in older groundwater (pre 1950s) than recently recharged groundwater. 7,13 Previous studies noted that sediment age can be important with respect to redox processes due to the preferential consumption of the most reactive components of sedimentary organic carbon by microbes over time. [38][39][40] In support of this hypothesis, McMahon et al 13 found that for aquifers composed of similar lithologies, concentrations of methane, dissolved organic carbon, and ammonium were higher in the aquifers with younger sediments than in aquifers with older sediments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13,37 Within a given lithology group, methane concentrations are typically higher in younger sediments than in older sediments, 13 and higher in older groundwater (pre 1950s) than recently recharged groundwater. 7,13 Previous studies noted that sediment age can be important with respect to redox processes due to the preferential consumption of the most reactive components of sedimentary organic carbon by microbes over time. [38][39][40] In support of this hypothesis, McMahon et al 13 found that for aquifers composed of similar lithologies, concentrations of methane, dissolved organic carbon, and ammonium were higher in the aquifers with younger sediments than in aquifers with older sediments.…”
Section: Discussionmentioning
confidence: 99%
“…While thermogenic methane was detected locally in the shallow subsurface in conjunction with some of the historic explosions that occurred in the LAB, 46 the methane distribution and isotopic systematics, and groundwater age results indicate that most excess methane in LA groundwater originates from microbial production in anoxic or suboxic conditions in the shallow aquifer systems, rather than the migration of deeper thermogenic methane in the hydrocarbon-bearing formations associated with oil fields in the basin. 7 Groundwater samples were collected in accordance with the protocols established by the USGS National Water-Quality Assessment (NAWQA) 34 and the USGS National Field Manual 35 after purging the equivalent of three casing-volumes from each well with a submersible pump. Samples were analyzed for a suite of inorganic, organic, and isotopic constituents; for a complete description of the sampling, analytical methods, quality assurance, and data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations